Five Dinuclear Lanthanide Complexes Based on 2,4-dimethylbenzoic Acid and 5,5′-dimethy-2,2′-bipyridine: Crystal Structures, Thermal Behaviour and Luminescent Property - Zhao, Jia-Yuan; Ren, Ning; Zhang, Ying-Ying; Tang, Kun; Zhang, Jian-Jun (Frontiers in Chemistry, 2021)
A series of new complexes, [Ln (2,4-DMBA)3(5,5′-DM-2,2′-bipy)]2 (Ln = Sm(1), Eu (2)), [Pr (2,4-DMBA)3 (5,5′-DM-2,2′-bipy)]2·0.5(C2H5OH) (3), [Ln (2,4-DMBA)3 (5,5′-DM-2,2′-bipy)]2·0.5(2,4-DMBAH)·0.25(5,5′-DM-2,2′-bipy) (Ln = Tb (4), Dy (5)) (2,4-DMBA = 2,4-dimethylbenzoate, 5,5′-DM-2,2′-bipy = 5,5′-dimethy-2,2′-bipyridine) were synthesized via hydrothermal reaction conditions. The complexes were characterized through elemental analysis, Infrared spectra (IR), Raman (R) spectra, UV-Vis spectra, single X-ray diffraction. Single crystal data show that complexes 1–5 are binuclear complexes, but they can be divided into three different crystal structures. The thermal decomposition mechanism of complexes 1–5 were investigated by the technology of simultaneous TG/DSC-FTIR. What’s more, the luminescent properties of complexes 1–2 and 4 were discussed, and the luminescence lifetime (τ) of complexes 2 and 4 were calculated.